Calender effect and portfolio management around the globe / Ahmad Fahmi Nazrin Dalimi - Dalimi, Ahmad Fahmi Nazrin (2016)
This paper examines the oil shocks dynamic impacts to different industry stock returns of Bursa Malaysia, namely; Consumer product, Finance, Industrial product, Plantation, Properties, Tin and Mining, and Trade and Services. The time frame for the analysis is from year 1997 to 2015 with weekly data observations. A multifactor market model motivated from CAPM and APT theory is employed to model the multifactor determinants of industry level stock returns in Malaysia. The model is tested using time-series and panel regression methods on different industry characteristics of the sample, namely; individual industry, overall industry, oil-dependent industry, non-oil dependent industry, big market size and small market size. The result indicates that oil shocks do influence the stock returns in Malaysia but the impacts is dynamic given different characteristic of the industry. In line with the theoretical expectations, oil dependent industries are more vulnerable to oil price shocks. This research not only highlights new emerging insights on stock pricing dynamics in Malaysia but also practical implications to investors, fund managers, and regulators on how to manage oil price shocks in Malaysian equity markets.